Brazilian CNPq research productivity fellows in the field of pneumology - Guimarães, Pedro Vitor Duarte; Sousa, Árlen Almeida Duarte de; Gomes, Hanna Gabriella Maurício; Oliveira, Fabrício Emanuel Soares de; Oliveira, Eduardo Araújo de; Martelli Júnior, Hercílio (Bionorte, 2025)
Objective: to describe the profile and scientific production of brazilian CNPq Research Productivity fellows in the field of Pulmonology. Materials and Methods: the study employed a cross-sectional census of 28 CNPq medical fellows, specialized in pulmonology. The curriculum vitae of each selected researcher was reviewed through the CNPq Lattes platform. Data extracted from the curriculum were analyzed using SPSS® 26.0, focusing on researcher demographics, publication metrics (published scientific articles, citations and H-index), and human resource training (scientific initiation, master’s and PhD supervision). Results: there was a predominance of males (64.3%), concentrated in São Paulo (42.8%), Rio Grande do Sul (21.4%), and Rio de Janeiro (17.8%). Collectively, they published 4,795 papers, averaging 171.25 articles per researcher, mainly indexed in Web of Science (80.77%) and Scopus (52.16%). In human resource training, they advised 445 scientific initiations, 472 Master’s students, and 346 PhD students. The median H-index at in this group of 28 researchers was 27. Conclusion: the researchers exhibit notable scientific productivity, highlighted by a significant H-index and active involvement in supervising scientific initiation, master's, and PhD students.